Primary Cytomegalovirus Phosphoprotein 65–Specific CD8(+) T-Cell Responses and T-bet Levels Predict Immune Control During Early Chronic Infection in Lung Transplant Recipients - Pipeling, Matthew R. (Oxford University Press, 2011)
Background. Cytomegalovirus (CMV) remains an important pathogen in solid organ transplantation, particularly lung transplantation. Lung transplant recipients (LTRs) mismatched for CMV (donor positive/recipient negative [D(+)R(−)]) are at highest risk for active CMV infection and have increased mortality. However, the correlates of immune control during chronic CMV infection remain incompletely understood. Methods. We prospectively studied 22 D(+)R(−) LTRs during primary CMV infection and into chronic infection. Immune responses during primary infection were analyzed for association with viral relapse during early chronic infection. Results. Primary CMV infection was characterized by a striking induction of T-box transcription factor (T-bet) in CD8(+) T cells. CMV-specific effector CD8(+) T cells were found to be T-bet(+). After primary infection, 7 LTRs lacked immune control with relapsing viremia during early chronic infection. LTRs with relapsing viremia had poor induction of T-bet and low frequencies of phosphoprotein 65 (pp65)–specific CD8(+) effector T cells during primary infection. However, frequencies of IE1-specific CD8(+) effector T cells during primary infection were not associated with early relapsing viremia. Conclusions. T-bet plays an important role in coordinating CD8(+) effector responses to CMV during primary infection. Moreover, CD8(+) T-bet induction and pp65-specific CD8(+) effector responses at the time of primary infection are important predictors of immune control of CMV during early chronic infection.